Visibility, Values, and Voters: The Informational Role of the Welfare State. (25th February 2014) - Gingrich, Jane
Abstract : How do citizens' preferences over social policy shape their vote choice? In this article, I argue that the relationship between individuals' values and voting behavior is powerfully conditioned by the informational structure of the welfare state. More visible welfare states provide citizens with greater information on social policy, allowing them to more easily connect these preferences to the political process. Where visibility is low, voters place less importance on social-policy issues in voting. I test this claim against data from 55 elections from the Comparative Study of Electoral Systems and the 1996 and 2006 International Social Survey Program. I find compelling evidence that where welfare-state visibility is high, voters attach more weight to spatial distance from parties in voting, are more likely to see welfare related issues as important, are better able to place parties on a left-right spectrum, and have more consistent policy preferences.